Frequency, underdiagnosis, and heterogeneity of epidermal growth factor receptor exon 20 insertion mutations using real‐world genomic datasets. Issue 2 (28th November 2022) - Viteri, Santiago; Minchom, Anna; Bazhenova, Lyudmila; Ou, Sai‐Hong Ignatius; Bauml, Joshua M.; Shell, Scott A.; Schaffer, Michael; Gu, Junchen; Rose, Jennifer B.; Curtin, Joshua C.; Mahadevia, Parthiv; Girard, Nicolas
Abstract : Epidermal growth factor receptor (EGFR) exon 20 insertion mutations (ex20ins) account for ≤ 12% of all EGFR‐mutant nonsmall cell lung cancers. We analysed real‐world datasets to determine the frequency of ex20ins variants, and the ability of polymerase chain reaction (PCR) and next‐generation sequencing (NGS) to identify them. Three real‐world United States NGS databases were used: GENIE, FoundationInsights, and GuardantINFORM. Mutation profiles consistent with in‐frame EGFR ex20ins were summarized. GENIE, FoundationInsights, and GuardantINFORM datasets identified 180, 627, and 627 patients with EGFR ex20ins respectively. The most frequent insertion region of exon 20 was the near loop ( 70%), followed by the far loop ( 30%) and the helical ( 3–6%) regions. GENIE, FoundationInsights, and GuardantINFORM datasets identified 41, 102, and 96 unique variants respectively. An analysis of variants projected that 50% of EGFR ex20ins identified by NGS would have been missed by PCR‐based assays. Given the breadth of EGFR ex20ins identified in the real‐world US datasets, the ability of PCR to identify these mutations is limited. NGS platforms are more appropriate to identify patients likely to benefit from EGFR ex20ins‐targeted therapies. Abstract : Three next‐generation sequencing (NGS) databases (GENIE, FoundationInsights and GuardantINFORM) were analyzed to estimate the frequency of exon 20 insertion (ex20ins) variants in epidermal growth factor receptor (EGFR)–mutant non‐small cell lung cancer (NSCLC). Results indicate 50% of ex20ins identified by NGS would have been missed by PCR and the near loop is the most frequent insertion site.